Serpent & dove - Mahurin, Shelby (Mahurin, Shelby. Serpent & Dove, 2019)
"The war between witches and Church is an ancient one, and Lou's most dangerous enemies bring a fate worse than fire. Unable to ignore her growing feelings, yet powerless to change what she is, a choice must be made."-- jacket